2021
DOI: 10.4018/ijhisi.20211001.oa22
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Using Smart Home Technologies to Support Older Adults

Abstract: This research explores the principle barriers to and facilitators of the use of Smart Home Technology, telemonitoring and telemedicine systems to support healthcare and enable older adults to maintain their independence. The research focuses on organizational rather than technological issues. Semi-structured interviews explored the perspectives of three populations of stakeholders (N = 17): managers of rest homes/retirement villages, technology developers in a university setting and older adults (age 65 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Sustainability and security are, therefore, vital aspects of the services needed to support such environments [2,30]. Technologies such as Smart Street Lighting [37] operate at all scales, while Intelligent Building Management [38] is needed to facilitate safety, regulate indoor climates, and provide both access and security at the dwelling scale. This perspective focuses on higher-level initiatives that draw together resources from the Smart Systems and Future Environments perspectives to profile patient interactions at all levels of the healthcare systems.…”
Section: Future Environmentsmentioning
confidence: 99%
“…Sustainability and security are, therefore, vital aspects of the services needed to support such environments [2,30]. Technologies such as Smart Street Lighting [37] operate at all scales, while Intelligent Building Management [38] is needed to facilitate safety, regulate indoor climates, and provide both access and security at the dwelling scale. This perspective focuses on higher-level initiatives that draw together resources from the Smart Systems and Future Environments perspectives to profile patient interactions at all levels of the healthcare systems.…”
Section: Future Environmentsmentioning
confidence: 99%
“…Through a survey of 111 older adults, the empirical study showed that the main elements of social-based aging user experience influence include system support, user interface design, and navigation. Alzahrani et al (2021) [11] explored the factors that influence the user experience of using smart home technology, remote monitoring, and telemedicine systems to support healthcare for older adults, using semi-structured interviews with older adults (65 years and older, N = 17), and showed that lack of technology, usability, cost, platform management, infrastructure, and privacy management influence the user experience of using smart homes for older adults. Kalimullah and Sushmitha (2017) [12] In order to investigate how to increase the use of mobile health apps by older adults, a research hypothesis was proposed to implement this idea by examining the factors that influence the user experience of user interface design elements in older adults.…”
Section: Elderly User Experiencementioning
confidence: 99%
“…2 Advances in mobile technology range from smartphones to infrared motion detectors, sensors built into beds and chairs (smart objects), and smart appliances, among others. 3 However, many of these technologies may be unavailable or hard to access in LMICs and in rural areas of high-income countries (HICs), particularly for older adults with lower health literacy and worse financial situations. In these settings, there is a need to implement and adapt novel cost-effective solutions to make digital technology as accessible as possible for underserved populations.…”
Section: Using Digital Technology To Find Original Ways To Follow The...mentioning
confidence: 99%